The Effect Of Giving Bay Leaf Boiled Water On Lowering Blood Pressure In 1-Month Injectable KB Acceptors At The Nining Midwife Clinic In 2022 - Lastri Rian; Farida Umamy; Emah Rohemah; Primastuti Widyaningrum (Jurnal EduHealth, 2024)
Background: the use of injectable contraceptives can cause high blood pressure or hypertension because injectable contraceptives contain the hormone progesterone which can cause hypertension due to the content of Depoprovera Medroxy Progesterone Acetat (DMPA). To find out the influence of Pandan leaf decoction on blood pressure on 1-month injectable KB acceptors Di at the Nining midwife Clinic in 2022. The studywas conducted in January-February at the Nining midwife Clinic in 2022. Method: this type of research is a pre-experimental research designs, this design is not a real experiment because there are still variables that contribute to the formation of the dependent variable. So the result of the experiment which is the dependent variable is not solely influenced by the independent variable. The population in this study is the entire acceptor KB injectable 1 month, the number of samples in this study as many as 17 acceptor KB injectable 1 month suffering from hypertension which shows that there is an effect of Pandan leaf decoction to decrease blood pressure in the acceptor KB injectable 1 month. Results: Hanalysis results obtained that 17 respondents had hypertension. The majority of respondents experienced Hypertension stage 1 as many as 12 people (70.6%), then who experienced pre hypertension 3 people (17.6%) and Hypertension stage 2 as many as 2 people (11.8%). The results of the analysis obtained blood pressure of respondents after consuming pandan leaf decoction majority of normal blood pressure as much as 15 people (88.2%) while Pre hypertension as much as 2 people (11.8%). There were changes in blood pressure in respondents who had previously experienced hypertension and after consuming pandan leaf decoction, the respondents ' blood pressure decreased by 15 people and 2 more people had decreased blood pressure but had not returned to normal completely. Conclusion: the results of this study can add insight and knowledge and can apply khususnya for family planning acceptor injection 1 month hypertension